2002
DOI: 10.1002/hup.390
|View full text |Cite
|
Sign up to set email alerts
|

Serological observations in patients suffering from acute manic episodes

Abstract: Although abnormalities of the immune system have been described in depression, information on serological alteration in acutely manic patients has been scarce. The present study undertook to investigate the levels of C-reactive proteins, circulating immune complexes, total immunoglobulins and immunoglobulin subclasses, complement proteins C3, C4, C6 and Factor B in the sera of 45 patients suffering from an acute manic episode. The findings were compared with assessments on the sera of 45 controls. The results … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
53
1

Year Published

2002
2002
2017
2017

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 94 publications
(57 citation statements)
references
References 17 publications
3
53
1
Order By: Relevance
“…All this is consistent with episode-specific differential gene expression of PTGDS and AKR1C3 as revealed in the present case. Alterations in inflammatory markers in serum of bipolar patients, such as cytokines, c-reactive protein and components of the complement system, have been reported previously (32)(33)(34)(35)(36)(37)(38). There might well be an interaction between the prostaglandin system found to be episodically regulated here, in the described case, and these inflammatory molecules, also in the CNS (35,39,40).…”
supporting
confidence: 72%
“…All this is consistent with episode-specific differential gene expression of PTGDS and AKR1C3 as revealed in the present case. Alterations in inflammatory markers in serum of bipolar patients, such as cytokines, c-reactive protein and components of the complement system, have been reported previously (32)(33)(34)(35)(36)(37)(38). There might well be an interaction between the prostaglandin system found to be episodically regulated here, in the described case, and these inflammatory molecules, also in the CNS (35,39,40).…”
supporting
confidence: 72%
“…C-reactive protein, a proinflammatory marker elevated in systemic inflammation and involved in chronic inflammatory processes, was elevated during both manic and depressive episodes [13]. In some studies such an elevation was found only in manic states [14,15], and in some it was higher in mania than in depression [16]. Depression has been accompanied by an elevation of C-reactive protein and treatment of the depressive symptoms resulted in its reduction [17,18].…”
Section: Introductionmentioning
confidence: 99%
“…These discrepancies may be explained by heterogeneity in mood state, methodological differences, and not controlling for known confounds, such as obesity (6). In addition to inflammatory markers, increasing production of antibodies (20 -22) and immunoglobulins (23,24) may be implicated with BD.…”
mentioning
confidence: 99%